Pengaruh Husnuzan terhadap Quarter Life Crisis pada Dewasa Dini Mahasiswa Psikologi Islam di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember (Fakultas Dakwah UIN KHAS Jember, 2022)
This research is motivated by the phenomenon of the many cases of Quarter Life Crisis (QLC) among students, including Islamic Psychology students at UIN Kiai Haji Achmad Siddiq Jember. This is because student age is the age at which individuals face QLC and starts from early adulthood. At this time, some developmental problems that arise in the form of many choices that must be planned for life in the future. This more or less makes the individual think hard, worried, anxious, and does not even rule out the possibility of experiencing depression. To minimize the level of QLC, we need a good mindset known as husnudzon which is one of the religious deepening practices that have indicators that are contrary to QLC. great influence. This study uses a quantitative approach with a descriptive survey type. The sampling technique used random sampling using the Slovin formula and obtained as many as 189 participants consisting of Islamic Psychology students at UIN KHAS Jember with an age range of 18-23 years. The instrument in the form of Husnuzan scale uses dimensions in IPTS (Islamic Positive Thinking Scale) whose items are compiled by researchers, and the QLC scale is adapted from Robbins & Wilner's theory. This scale has been through a validity test with the results of the overall item r count > r table (r table of 0.1420 for = 5%). The results of the scale reliability test were declared reliable, indicated by the Cronbach's Alpha value of 0.785. The analysis of this research uses the formula of Simple Linear Regression Analysis. The results showed that there was a very low negative effect of the Husnuzan variabel on the QLC of 8.4%.